Eksplorasi Kemampuan Motorik Halus Anak Usia Dini Melalui Kegiatan Seni Rupa di KB-BA Restu 1 Malang - Nur Alifia Sinta; Usep Kustiawan (Atthiflah: Journal of Early Childhood Islamic Education, 2026)
Fine motor development is an important aspect of early childhood because it is closely related to hand-eye coordination skills required in various learning activities. Preliminary observations indicated that some children experienced difficulties in holding writing tools, controlling hand movements, and completing drawing and coloring activities according to their developmental stages. The study aimed to describe the implementation of art activities in developing fine motor skills among children age 4-6 years integrated with islamic values at KB-BA Restu 1 Malang. The study employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The findings revealed that art activities were conducted through various form, including drawing, coloring, collage, color blowing techniques, finger painting, and simple construction-making activities. These activities contributed to the development of children’s fine motor skills as evidenced by improved hand-eye coordination, accuracy in using tools and materials, and better control of hand movements. Furthermore, art activities served as a medium for instilling Islamic values such as discipline, responsibility, patience, cleanliness, and gratitude. The study concludes that varied art activities integrated with Islamic values can effectively support early childhood fine motor development. Teachers are encouraged to maintain diverse art activities and provide stimulation according to children’s developmental characteristics